Destination Life Cycle of Goan Beach Shacks - R. Antony Sathish Benadict, Helic Mario Barretto, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The study analyzes the stage of the Destination Life Cycle beach shacks lies at present in the State of Goa. Beach shacks are temporary restaurants located on the beach serving home-cooked food along with beverages. The study is quantitative in nature, based on a random sample of 250 respondents, collected during October 2018 to May 2019 using structured questionnaire. The statistical tools used are chi-square test, Butler’s Tourism Area Life Cycle model, and the Additive Points scoring technique to model the Destination Life Cycle stage. The findings indicate that beach shacks lie in the Development Stage of the Destination Life Cycle based on the average number of tourist visits, average amount spent by tourists per visit, per person at a shack, average profits per month, and average monthly operating expenses of a shack. However, they lie in the Involvement Stage based on the average number of people employed at shacks.